2022
DOI: 10.1002/smm2.1147
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable, self‐healable, and breathable biomimetic iontronics with superior humidity‐sensing performance for wireless respiration monitoring

Abstract: Stretchable, self-healing, and breathable skin-biomimetic-sensing iontronics play an important role in human physiological signal monitoring and human-computer interaction. However, previous studies have focused on the mimicking of skin tactile sensing (pressure, strain, and temperature), and the development of more functionalities is necessary. To this end, a superior humidity-sensitive ionic skin is developed based on a self-healing, stretchable, breathable, and biocompatible polyvinyl alcohol-cellulose nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 72 publications
0
44
0
Order By: Relevance
“…18,19 Among them, hydrogels are considered to be a promising material for promoting wound healing due to their similar flexibility to the native extracellular matrix (ECM), excellent biocompatibility compatible with the skin, good selfhealing and ability to provide a moist environment. [20][21][22][23][24][25][26][27][28][29][30] To date, many smart hydrogel dressings have been developed…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Among them, hydrogels are considered to be a promising material for promoting wound healing due to their similar flexibility to the native extracellular matrix (ECM), excellent biocompatibility compatible with the skin, good selfhealing and ability to provide a moist environment. [20][21][22][23][24][25][26][27][28][29][30] To date, many smart hydrogel dressings have been developed…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Among them, hydrogels are considered to be a promising material for promoting wound healing due to their similar flexibility to the native extracellular matrix (ECM), excellent biocompatibility compatible with the skin, good self-healing and ability to provide a moist environment. 20–30 To date, many smart hydrogel dressings have been developed for wound management. 31,32 Various hydrogels with inherent or additional antibacterial properties have been used for inhibiting infection and preventing the chronic phase of the wound.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al fabricated a highly ion-conductive and cellulose nanofibril (CNF)-reinforced organogel with extreme-temperature tolerance for flexible humidity sensors . Wu and co-workers successfully constructed a series of multifunctional soft gel polymers based on different biological macromolecules, which could serve as stretchable, highly sensitive, and environmentally-tolerant gas sensors with wireless operation. Notably, κ-carrageenan (κ-CG) as a biomacromolecule is a linear sulfated polysaccharide extracted from natural seaweed and possesses superior biocompatibility, nontoxicity, and excellent gel-forming capabilities, which is also regarded as a promising material to improve the toughness of hydrogels. , For instance, Tao et al reported a tactile hydrogel sensor based on a micropyramid-patterned double-network ionic hydrogel consisting of carrageenan and PAM chains, which exhibited fascinating application prospects in flexible electronics . Additionally, previous studies have suggested that adding metal ions into hydrogels containing poly­(acrylic acid) chains is also an effective strategy to further enhance their mechanical properties. The added metal ions can form strong coordination bond interactions with the carboxyl groups onto poly­(acrylic acid) chains, which remarkably increase the cross-linking densities of hydrogel networks and endow the resulting hydrogel with excellent stretchability and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…This significant thermoacoustic effect observed certifies that SLGF has an excellent ability to generate heat (Joule heat) and transfer heat. Compared to other types of strain or temperature sensors, such as highly-stretchable hydrogel sensors, [39][40][41][42][43] the SLGF sensors are crucially in applications that require both strain monitoring and thermal control.…”
Section: Introductionmentioning
confidence: 99%